Assessment of the Radiometric Calibration Consistency of Reflective Solar Bands between Terra and Aqua MODIS in Upcoming Collection-7 L1B - Aisheng Wu; Xiaoxiong Xiong; Amit Angal; Qiaozhen Mu; Sherry Li (Remote Sensing, 2023)
Two MODIS sensors onboard the Terra and Aqua spacecraft have been successfully operating for over twenty-three and twenty-one years, respectively, providing the worldwide user community with high-quality imagery and radiometric Earth observations of the land, atmosphere, cryosphere, and oceans. This study provides an assessment of the radiometric calibration stability and consistency of Terra and Aqua MODIS RSB using the L1B from the upcoming Collection 7 release. Several independent vicarious approaches based on measurements from the Libya-4 desert, Dome C, DCC, and SNO are used to assess the calibration stability at the beginning of scan, nadir, and end of scan. Results indicate that both Terra and Aqua RSB are stable to within 1% over their mission periods. Comparison of the normalized reflectances with either a BRDF model or a common reference sensor provides a radiometric assessment of Terra and Aqua calibration consistency. Comparison results show the VIS/NIR bands are in good agreement around the nadir and at the beginning of the scan for all the approaches. For cases at the end of the scan, the agreement varies depending on the approach but is typically within ±2%. The differences observed in the SWIR bands are slightly larger than the VIS/NIR bands, which are likely due to their high sensitivity to atmospheric conditions and relatively larger electronic crosstalk impact on the Terra instrument.